An Assessment on Level of Stress among the Workers in Cotton Mill Industries in India - Ashifa, K.M. (International Journal of Psychosocial Rehabilitation, 2020)
In this fast moving world, people are held up both professionally and personally. The physical and mental effort people put in different works are very high. Hence majority of the people around the world are prone to stress. Human daily life is full of stress and tension. Work stress is an increasing concern for administrations today. Stress can be defined as a likely situation in which people face constrictions, opportunities. Stress is the reply of people to the irrational pressure or difficulties placed on them. The employer will take many measures to condense employee stress instantaneously and therefore increase his or her efficiency and health, physical and mental skills, attentiveness, self-esteem and overall efficiencies. This study aims to identify the physical and psychological symptoms of stress and to reveal the purpose of managing the stress which helps the employees to perform their work in a better way. It was focused on analysis of level of stress among the workers in cotton Mills in Rajapalayam district, Tamil Nadu, South India. The study revealed that stress in the working conditions is due to work load, poor salary, Time pressures and deadlines, lack of security offered by the Cotton Mills.